PENGARUH LINGKUNGAN KERJA DAN PERILAKU KERJA TERHADAP KINERJA PEGAWAI - Wisna Wardani Sidik; Samdin Samdin; Dedy Takdir Syaifuddin (Pascasarjana Universitas Halu Oleo, 2018)
This research was conducted with the aim to determine the effect of the work environment and work behavior on employee performance at the Konawe Utara District Secretariat Office. The data used in the study were interview data and analyzed using SEM analysis using 109 respondents.The results of the study obtained several conclusions, among others: (1) The work environment and work behavior have a reciprocal influence, meaning that the work environment has an influence on work behavior and work behavior influences the work environment at the Konawe Utara District Secretariat office. (2) The work environment improves employee performance at the Konawe Utara District Secretariat because the work environment has a positive and significant influence. (3) Work behavior cannot affect employee performance at the Konawe Utara District Secretariat because employees have established work behavior with self-control, integrity, trust, professionalism, cooperation and attendance that supports employee performance so that work behavior does not affect performance employee. (4) The results of the description analysis show the work environment, work schedule and employee performance including being assessed by respondents.Keywords: work condition, work behaviour and clerk performance